ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADA INDUSTRI TEKSTIL DI KOTA DENPASAR - Ayuningati, Ghina Rachmita; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 1 (2024): Vol.13.No.1. JANUARI 2024[1-90]DO - 10.24843/EEP.2024.v13.i01.p01, 2024)
The manufacturing sector plays a crucial role in supporting a country's economic growth. Many countries view this sector as a primary driver of economic development due to its significant advantages compared to other sectors. For this reason, industrialization strategies are often employed to achieve societal well-being. One example is the textile industry in the Bali Province, which holds substantial potential and ranks third highest in each district. The objective of this study is to analyze the impact of capital, labor, and technology on textile industry production in Denpasar City. The study utilizes both primary and secondary data. It will involve the participation of 90 respondents as samples, using the Proporsionate Stratified Random Sampling approach, drawn from a population of 983 entrepreneurs operating in the textile industry sector in Denpasar City. Multiple linear regression analysis will be employed. The findings of this study indicate that capital, labor, and technology collectively have a significant impact on production within the textile industry sector in Denpasar City. Additionally, individually, capital, labor, and technology also make positive and significant contributions to textile industry production in the region. These findings reinforce the hypothesis that capital, labor, and technology variables play a crucial role in influencing production. Keywords: capital, labor, technology, production